Acute respiratory distress syndrome and mechanical ventilation: ups and downs of an ongoing relationship trap - Haberthür, Christoph; Seeberger, Manfred D. (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
During the early 20th century, patients suffering from acute severe pulmonary diseases died because medicine lacked the possibility to sufficiently treat lung failure (i.e., to assure ventilation with adequate oxygenation and exhalation of carbon dioxide) until lung healing occurred.